Spinel-based near-infrared fluorescent powder and preparation method thereof

Through the chemical formula of spinel-based LiAl(4.96-x)BxO(8-1.5x)Nx:0.04Cr, a near-infrared phosphor was prepared by high-temperature sintering method, which solved the problems of low luminous intensity, narrow half-maximum width and poor photothermal stability of existing materials, and achieved a high efficiency and stable near-infrared light source.

CN119529826APending Publication Date: 2025-02-28LANZHOU JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411737604.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing near-infrared fluorescent materials have problems such as low luminous intensity, narrow half-maximum width, and poor photothermal stability, which is difficult to meet the needs of wide emission bands and high-efficiency near-infrared light sources.

Method used

Using the chemical formula of spinel-based LiAl(4.96-x)BxO(8-1.5x)Nx:0.04Cr, LiOH, AlF3, BN and Cr2O3 were mixed in a certain proportion by synthesis method and sintered at high temperature to prepare a near-infrared phosphor with high luminescence efficiency and stable chemical properties.

Benefits of technology

It has achieved near-infrared phosphors with high luminous efficiency, stable chemical properties, and small brightness changes at high temperatures, which are suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529826A_ABST
    Figure CN119529826A_ABST
Patent Text Reader

Abstract

The invention discloses spinel-based near-infrared fluorescent powder and a preparation method thereof.The prepared spinel-based near-infrared fluorescent powder is LiAl (4.96-x) BxO (8-1.5 x) Nx: 0.04 Cr, x is larger than or equal to 0 and smaller than or equal to 1, raw materials are fully mixed and ground, the temperature is raised to 550 DEG C in the air atmosphere and preheated for 3 h, then the temperature is raised to 1200 DEG C, heat preservation is conducted for a period of time, finally, after the temperature is reduced to the room temperature, the materials are taken out and ground, and the spinel-based near-infrared fluorescent powder is obtained. The spinel-based NIR fluorescent powder is obtained. According to the preparation method of the spinel-based NIR fluorescent powder, common metal hydroxides and fluorides are adopted as raw materials, the obtained fluorescent powder is high in luminous efficiency, stable in chemical property and small in brightness change at high temperature, and the preparation method is simple, easy to implement and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorescent powder for LED, and relates to a spinel-based near-infrared fluorescent powder and a preparation method thereof. Background Art

[0002] Near infrared light (NIR) has strong penetration, low thermal effect and non-destructiveness, and is widely used in liquid vision lighting, monitoring systems, iris recognition, infrared spectroscopy analysis and biological imaging. In recent years, compared with traditional light sources, NIR fluorescent conversion light-emitting diodes (NIR PC-LEDs) have the advantages of small size, low price and high light efficiency, and have attracted widespread attention. They have been widely used in food analysis, plant growth, night vision, biomedical imaging and other fields, and have been accepted by more and more application companies, playing an important role in the actual industrial and agricultural production process. In these applications, there is an urgent need for near-infrared light sources with a wide emission band and high efficiency. Although traditional NIR light sources such as incandescent lamps and halogen lamps can present a wide emission spectrum from visible light to near infrared, their low efficiency, short life, large size and high operating temperature have hindered their practical application. As a light conversion material, phosphor is one of the key components of pc-LED, and with the evolution of demand in the development of the times, different types of phosphor materials have been developed and applied. In recent years, transition metal ions Cr with wide near-infrared luminescence characteristics have been widely used. 3+ Research on near-infrared fluorescent materials doped with inorganic compounds is quite hot. This is because Cr 3+ The 3d energy level of Cr is sensitive to the surrounding crystal field environment. Inorganic compounds with different coordination structures produce different crystal field strengths, which results in 3+ The emission spectrum peak wavelength position and half-peak width are different. Although some blue light-excited near-infrared luminescent materials have been reported, there are still some problems such as low luminescence intensity, narrow half-peak width, and poor photothermal stability. Summary of the invention

[0003] The present invention aims to provide a spinel-based near-infrared phosphor and a preparation method thereof. The obtained fluorescent material has high luminous efficiency, stable chemical properties, small brightness change at high temperature, and a simple and easy preparation method suitable for large-scale industrial production.

[0004] To achieve the above purpose, the chemical formula of the near-infrared phosphor of the present invention is: LiAl (4.96-x) B x O (8-1.5x) N x :0.04Cr, 0≤x≤1; the excitation wavelength range is 300-700nm, the emission wavelength range is 600-900nm, and the emission peak is at 714nm.

[0005] The method for preparing the spinel-based near-infrared phosphor is as follows: (4.96-x) B x O (8-1.5x) N x :0.04Cr chemical element stoichiometric ratio weighing LiOH, AlF 3 , BN and Cr 2 O 3 The raw materials are fully mixed and ground to obtain a mixture, which is placed in a boron nitride crucible, and the mixture is preheated at 500-600°C for 2-5 hours in an air atmosphere, and then heated to 1200±100°C at a heating rate of 2-10°C / min, kept warm for 2-10 hours, and finally cooled to room temperature with the furnace to obtain the spinel-based near-infrared phosphor.

[0006] Another object of the present invention is to provide a light-emitting device, comprising a light source and a light-emitting material excited by the light source, wherein the light-emitting material is the above-mentioned spinel-based near-infrared light-emitting material, and the light source is an LED light source with a wavelength of 300~700nm, preferably an LED light source with a wavelength at 400±10nm and 570±10nm.

[0007] Compared with the prior art, the present invention has the following beneficial technical effects: The invention provides a method for preparing a spinel-based nitrogen oxide NIR phosphor, using common LiOH, AlF 3 , BN, Cr 2 O 3 The spinel-based nitrogen oxide NIR phosphor prepared by using 2-nitrogen-doped iodine as raw material has the advantages of good crystallinity, high luminous efficiency, stable chemical properties, and small brightness change at high temperature. The method is simple and easy to operate, with a wide process window, and is suitable for large-scale industrial production.

[0008] Luminescence mechanism LiAl 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr as an example, the present invention is reported in LiAl 5 O 8 Cr 3+ Based on the optimal doping amount, the B 3+ +N 3- →Al 3+ +O 2- According to relevant reports, LiAl 5 O 8 With inverse spinel structure, LiAl 4.16 B 0.8 O 6.8 N 0.8:0.04Cr diffraction peak ( Figure 1 ) and cubic LiAl 5 O 8 phase (ICSD number: 10480), and the space group is P4332 (number: 212), indicating that LiAl 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr pure product was successfully synthesized. Figure 2 As shown, LiAl 5 O 8 The structure consists of 4-coordinated and 6-coordinated Al 3+ However, due to the Cr 3+ (r=0.615Å, CN=6) and Al 3+ (r=0.535Å, CN=6) and Al 3+ (r=0.39 Å, CN=4) have similar ionic radii, Cr 3+ In the 6-fold coordination, Cr has a strong coordination field stabilization energy. 3+ Dopants tend to occupy the octahedral Al 3+ Site. 3+ (r = 0.11Å, CN = 4) and N 3- The radius of (r=1.46Å, CN=4) is smaller than that of Al 3+ (r = 0.39Å, CN = 4) and O 2- (r=1.38 Å, CN=4). Considering B 3+ +N 3- →Al 3+ +O 2- The charge and effective ionic radius of the ion, B 3+ The ions should mainly replace Al in the 4-fold coordination 3+ .

[0009] Cr 3+ Ions belong to 3 d 3 The electronic configuration, in octahedral symmetry, d 3 The configuration produces two quaternions, namely 4 F and 4 P, according to Hund's rule, 4F terms are lower than 4P. In addition to these quartic terms, there are several double terms. 4F terms are divided into 4 A 2g , 4 T 2g and 4 T g Level, 2E level comes from 2G term, luminescence and excitation spectra depend on 2E and 4 T2 The relative position between levels. Figure 3 LiAl 4.16 B 0.8 O 6.8 N 0.8 : UV-diffuse reflectance spectrum of 0.04Cr. The sample has a wavelength of 264nm (37867cm -1 )、376nm(26588cm -1 ) and 562nm (17788cm -1 ) shows a broad peak, and the two main broad absorption bands observed at 376 nm and 562 nm are derived from the octahedral Cr 3+ The spin of the ion allows dd transitions, which are assigned to 4 A 2g (F) / 4 T g (F) and 4 A 2g (F) / 4 T 2g (F), the band at 264 nm in the ultraviolet region is attributed to Cr 6+ -O 2- charge transfer band.

[0010] Figure 4 The room temperature LiAl 4.16 B 0.8 O 6.8 N 0.8 : The excitation spectrum and emission spectrum of 0.04Cr. The excitation spectrum consists of several peaks, with peak positions at 398nm (25118cm -1 )、410nm (24383 cm -1 )、469nm(21316 cm -1 ) and 562nm (17788 cm -1 ), the peaks at 398nm and 410nm belong to the spin-allowed 4 A 2g (F) / 4 T g (F) transition, which is split into approximately 735 cm due to D3d distortion -1 , 398 nm is in the ultraviolet region, with higher energy, and is usually used to excite the high-energy dd transition of Cr³⁺. This wavelength is suitable for the excitation of Cr³⁺ ions under higher crystal field symmetry, which can effectively promote the transition of Cr³⁺ from low energy level to high energy level, and produce a strong excited state. The broad peak near 562 nm is spin-allowed 4 A 2g (F) / 4 T2g (F) transition, the energy of the photoexcited electron transition is moderate, which can effectively excite Cr³⁺ ions while avoiding non-radiative transitions caused by over-excitation, thereby improving the fluorescence efficiency. Therefore, 398 nm and 562 nm belong to LiAl 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr preferred excitation wavelength. In addition to these spin-allowed bands, at 469nm (21316cm -1 ), 483 nm (20698 cm -1 ) and 494 nm (20237 cm -1 ) were also observed at 570 nm, which is caused by the transition within the configuration. This makes the Cr³⁺-doped phosphors effectively excited under visible light. 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr emission wavelength is 714 nm, corresponding to Cr 3+ Spin forbidden in six-fold coordination 2 E→ 4 A 2 At the same time, the sample exhibits good fluorescence performance at the emission wavelength of 714 nm, which is suitable for a variety of applications in the infrared spectrum. 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr's preferred emission wavelength.

[0011] The LiAl 5 O 8 and LiAl 4.16 B 0.8 O 6.8 N 0.8 The density of states (DOS) is as follows: Figure 5 The calculation results show that LiAl 4.16 B 0.8 O 6.8 N 0.8 The direct band gap width is 4.96 eV, which is smaller than LiAl 5 O 8 The band gap width of LiAl is 6.35eV. 5 O 8 and LiAl 4.16 B 0.8 O 6.8 N 0.8The valence band top is mainly composed of Al 2p orbital composition, the conduction band is mainly composed of O 2p Orbital composition. The size of the band gap is related to the strength of the bond between the valence electrons and their atoms. As the ionicity of the compound increases, the valence electrons will move closer to the native atoms, and the bonds will be tighter, which means that more energy is required to break the bonds. LiAl 4.16 B 0.8 O 6.8 N 0.8 The band gap is larger than LiAl 5 O 8 Small, indicating that its ionicity is weak, which indicates that B 3+ +N 3- Solid solution substitution Al 3+ +O 2- After that, the covalency is enhanced, and the electron cloud effect caused by the enhanced covalency will promote the energy level splitting to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is the X-ray diffraction spectrum of Example 1 of the present invention; Figure 2 LiAl 5 O 8 :0.04Cr crystal structure along c-axis and b-axis; Figure 3 is the UV-diffuse reflectance spectrum of Example 1 of the present invention; Figure 4 is the excitation and emission spectra of Example 1 of the present invention; Figure 5 For Example 1 of the present invention and LiAl 5 O 8 The band gap and density of states; Figure 6 The emission spectra of Example 1 of the present invention at different temperatures, wherein the excitation wavelength is 570 nm; Figure 7 is the X-ray diffraction spectrum of Example 2 of the present invention; Figure 8 The excitation and emission spectra of Example 2 of the present invention; Fig. 9 is the X-ray diffraction spectrum of Example 3 of the present invention; Fig.10 The excitation and emission spectra of Example 3 of the present invention; Fig.11 is the X-ray diffraction spectrum of Example 4 of the present invention; Fig.12 The excitation and emission spectra of Example 4 of the present invention; Fig.13is the X-ray diffraction spectrum of Example 5 of the present invention; Fig.14 is the excitation and emission spectra of Example 5 of the present invention; Fig.15 is the X-ray diffraction spectrum of Example 6 of the present invention; Fig.16 The excitation and emission spectra of Example 6 of the present invention; Fig.17 is the X-ray diffraction spectrum of Example 7 of the present invention; Fig.18 : are the excitation and emission spectra of Example 7 of the present invention; Fig.19 is the X-ray diffraction spectrum of Example 8 of the present invention; Fig. 20 The excitation and emission spectra of Example 8 of the present invention; DETAILED DESCRIPTION

[0013] The present invention will be further explained below in conjunction with the embodiments.

[0014] Example 1 LiAl 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr According to LiAl 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat to 1200°C and sintered for 6 hours and then cooled to room temperature; taken out and crushed to obtain NIR phosphor LiAl 4.16 B 0.8 O 6.8 N 0.8 :0.04Cr.

[0015] Structural characterization and performance evaluation of products Figure 1 LiAl 4.16 B 0.8 O 6.8 N 0.8 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Figure 2 LiAl 5 O 8:0.04Cr crystal structure along c-axis and b-axis; Figure 3 LiAl 4.16 B 0.8 O 6.8 N 0.8 : UV-diffuse reflectance spectrum of 0.04Cr; Figure 4 LiAl 4.16 B 0.8 O 6.8 N 0.8 : Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the optimal excitation wavelength being between 400 nm and 570 nm; the main emission wavelength is around 714 nm; Figure 5 LiAl 4.16 B 0.8 O 6.8 N 0.8 and the band gap and density of states of LiAl5O8; Figure 6 LiAl 4.16 B 0.8 O 6.8 N 0.8 The emission spectrum of 0.04Cr changes at different temperatures, where the excitation wavelength is 576 nm. The results show that at a high temperature of 473.15K, the luminous intensity of the phosphor remains at about 80% of that at 273.15K, indicating that the phosphor has good brightness and color stability at high temperatures.

[0016] Example 2 LiAl 4.86 B 0.1 O 7.85 N 0.1 :0.04Cr According to LiAl 4.86 B 0.1 O 7.85 N 0.1 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat up to 1200°C and sintered for 6 hours before cooling to room temperature; taken out and crushed to obtain red phosphor LiAl 4.86 B 0.1 O 7.85 N 0.1 :0.04Cr. Structural characterization and performance evaluation of products Figure 7 LiAl 4.16 B 0.1 O 6.8 N 0.1 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Figure 8 LiAl 4.16 B 0.1 O 6.8 N 0.1 : Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the best excitation wavelengths at 400 nm and 570 nm; the main emission wavelength is around 714 nm.

[0017] Example 3 LiAl 4.76 B 0.2 O 7.7 N 0.2 :0.04Cr According to LiAl 4.76 B 0.2 O 7.7 N 0.2 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat up to 1200°C and sintered for 6 hours before cooling to room temperature; taken out and crushed to obtain red phosphor LiAl 4.76 B 0.2 O 7.7 N 0.2 :0.04Cr.

[0018] Structural characterization and performance evaluation of products Fig. 9 LiAl 4.16 B 0.2 O 6.8 N 0.2 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Fig.10 LiAl 4.16 B 0.2 O 6.8 N 0.2: Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the best excitation wavelengths at 400 nm and 570 nm; the main emission wavelength is around 714 nm.

[0019] Example 4 LiAl 4.66 B 0.3 O 7.55 N 0.3 :0.04Cr According to LiAl 4.66 B 0.3 O 7.55 N 0.3 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat to 1200°C and sintered for 6 hours and then cooled to room temperature; taken out and crushed to obtain NIR phosphor LiAl 4.66 B 0.3 O 7.55 N 0.3 :0.04Cr.

[0020] Structural characterization and performance evaluation of products Fig.11 LiAl 4.16 B 0.3 O 6.8 N 0.3 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Fig.12 LiAl 4.16 B 0.3 O 6.8 N 0.3 : Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the best excitation wavelengths at 400 nm and 570 nm; the main emission wavelength is around 714 nm.

[0021] Example 5 LiAl 4.56 B 0.4 O 7.4 N 0.4 :0.04Cr According to LiAl 4.56 B 0.4 O 7.4 N 0.4 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3, BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat to 1200°C and sintered for 6 hours and then cooled to room temperature; taken out and crushed to obtain NIR phosphor LiAl 4.56 B 0.4 O 7.4 N 0.4 :0.04Cr.

[0022] Structural characterization and performance evaluation of products Fig.13 LiAl 4.16 B 0.4 O 6.8 N 0.4 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Fig.14 LiAl 4.16 B 0.4 O 6.8 N 0.4 : Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the best excitation wavelengths at 400 nm and 570 nm; the main emission wavelength is around 714 nm.

[0023] Example 6 LiAl 4.46 B 0.5 O 7.25 N 0.5 :0.04Cr According to LiAl 4.46 B 0.5 O 7.25 N 0.5 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat to 1200°C and sintered for 6 hours and then cooled to room temperature; taken out and crushed to obtain NIR phosphor LiAl 4.46 B 0.5 O 7.25 N 0.5 :0.04Cr.

[0024] Structural characterization and performance evaluation of products Fig.15 LiAl 4.16 B 0.5 O6.8 N 0.5 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Fig.16 LiAl 4.16 B 0.5 O 6.8 N 0.5 : Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the best excitation wavelengths at 400 nm and 570 nm; the main emission wavelength is around 714 nm.

[0025] Example 7 LiAl 4.36 B 0.6 O 7.1 N 0.6 :0.04Cr According to LiAl 4.36 B 0.6 O 7.1 N 0.6 :0.04Cr stoichiometric ratio weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat to 1200°C and sintered for 6 hours and then cooled to room temperature; taken out and crushed to obtain NIR phosphor LiAl 4.36 B 0.6 O 7.1 N 0.6 :0.04Cr.

[0026] Structural characterization and performance evaluation of products Fig.17 LiAl 4.16 B 0.6 O 6.8 N 0.6 : The X-ray diffraction spectrum of 0.04Cr shows that the sample has a good crystal structure; Fig.18 LiAl 4.16 B 0.6 O 6.8 N 0.6 : Excitation and emission spectra of 0.04Cr. The excitation wavelength of the phosphor is between 300 and 700 nm, with the best excitation wavelengths at 400 nm and 570 nm; the main emission wavelength is around 714 nm.

[0027] Example 8 LiAl 3.96 BO 6.5N:0.04Cr According to LiAl 3.96 BO 6.5 N:0.04Cr weigh LiOH, AlF 3 , BN and Cr 2 O 3 , mixed, fully ground and placed in a boron nitride crucible; the crucible was placed in a tube furnace, sintered at 550°C for 3 hours in air, then continued to heat up to 1200°C and sintered for 6 hours before cooling to room temperature; taken out and crushed to obtain red phosphor LiAl 3.96 BO 6.5 N:0.04Cr.

[0028] Structural characterization and performance evaluation of products Fig.19 LiAl 4.16 BO 6.8 The X-ray diffraction spectrum of N:0.04Cr shows that the sample has a good crystal structure; Fig. 20 LiAl 4.16 BO 6.8 Excitation and emission spectra of N:0.04Cr. The excitation wavelength of this phosphor is between 300 and 700 nm, with the best excitation wavelengths between 400 nm and 570 nm; the main emission wavelength is around 714 nm.

Claims

1. A spinel-based near-infrared phosphor, characterized in that: The chemical formula of the near-infrared phosphor is: LiAl (4.96-x) B x O (8-1.5x) N x :0.04Cr, 0≤x≤1; the excitation wavelength range is 300-700nm, the emission wavelength range is 600-900nm, and the emission peak is at 714nm.

2. A method for preparing the spinel-based near-infrared phosphor according to claim 1, characterized in that: According to LiAl (4.96-x) B x O (8-1.5x) N x LiOH, AlF3, BN and Cr2O3 are weighed as raw materials in a chemical element stoichiometric ratio of Cr:0.04Cr, the raw materials are fully mixed and ground to obtain a mixture, which is put into a boron nitride crucible, and the mixture is preheated at 500-600°C for 2-5h in an air atmosphere, and then heated to 1200±100°C at a heating rate of 2-10°C / min, kept warm for 2-10h, and finally cooled to room temperature with the furnace to obtain the spinel-based near-infrared phosphor.

3. A light-emitting device, comprising a light source and a light-emitting material excited by the light source, characterized in that: The luminescent material is the spinel-based near-infrared phosphor as described in claim 1.